Kinematic and electromyographic behaviour of basketball players injured and healthy ankles during the jump onto an unstable board - Castroa, M. A.; Janeirab, M. A.; Fernandesc,O.; Cunhad, L. M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to identify kinematic and electromyographic differences of jumps performed by basketball players with healthy and previously sprained ankles. 25 elite basketball players with healthy (n=17) and already sprained ankles (n=28) jumped five times in unipodal support from a stable surface onto a round Freeman board. During the jump the flight phase of those athletes with already sprained ankles was shorter which may indicate less preparation time for the moment of contact with the surface and for the respective load. When landing, they also positioned their ankle in a more plantar flexion and generally, the contraction of their foot musles was stronger than that of the healthy athletes. The groups' differing movement behaviour of the lower leg possibly explains resulting ankle injuries. These results indicate that it might be necessary to train athletes to jump in -safe positions- in order to prevent ankle sprains.